Indoor Biomass Fuel Smoke Exposure as a Risk Factor for Chronic Obstructive Pulmonary Disease (COPD) for Women of Rural Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Background: Chronic Obstructive Pulmonary Disease (COPD) is of public health importance. Indoor biomass (wood, cowdung etc) smoke exposure from cooking is associated with respiratory conditions and may predispose to COPD. The objective of this study was to evaluate the risk of biomass smoke exposure and COPD.Methods: A cross sectional study was conducted at a rural setting of Bangladesh. Rural women over 40 years and exposed to biomass fuel, liquid petroleum gas or natural gas smoke were evaluated using a questionnaire and their lung function was assessed using a portable spirometry.Results: The overall prevalence of COPD in the rural women was 20.4%. It was significantly higher in women using biomass fuel for cooking than in those using natural gas/LPG (p